2013
DOI: 10.3233/ies-130498
|View full text |Cite
|
Sign up to set email alerts
|

The influence of circadian rhythms on peak isokinetic force of quadriceps and hamstring muscles

Abstract: BACKGROUND: Circadian rhythms, and their potential influence on athletic performance, have been the subject of a number of investigations. OBJECTIVE: This study aimed to determine the influence of circadian rhythms on the peak isokinetic force of the quadriceps and hamstring muscle groups, and the relationship of cortisol level with these measures. METHODS: Twelve male and twelve female participants completed maximal isokinetic flexion and extension movements of their dominant leg at 60 • /s using an isokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Although the present study was not designed to determine how or why sleep quantity affects performance, it is likely that diurnal variation in hormonal levels played a role ( 23 , 26 , 29 ). For example, cortisol levels are elevated upon waking up ( 22 ), and decrements in performance have been correlated with levels of salivary cortisol in the morning ( 24 ). Consistent with altered stress levels, we report that morning practice was related to less sleep quantity (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study was not designed to determine how or why sleep quantity affects performance, it is likely that diurnal variation in hormonal levels played a role ( 23 , 26 , 29 ). For example, cortisol levels are elevated upon waking up ( 22 ), and decrements in performance have been correlated with levels of salivary cortisol in the morning ( 24 ). Consistent with altered stress levels, we report that morning practice was related to less sleep quantity (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although time of day is often taken into consideration when sport-specific training is performed, strength and conditioning sessions are oftentimes conducted throughout the day. Muscular strength and outcome variables associated with strength may also be affected by time of day as isolated knee torque exercises ( 8 , 24 , 29 ) and dynamic sport performance tests ( 5 , 20 , 27 , 28 ) have also been reported to be greater in the afternoon compared with the morning.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies (Sinclair et al, 2013;Anderson et al, 2016) showed an increase and decrease. One study (Sinclair et al, 2013) showed an increase in cortisol levels in men and a decrease in women. One study (Anderson et al, 2016) showed an acute increase in salivary cortisol levels after the first intervention and a chronic increase after 12 weeks.…”
Section: Resultsmentioning
confidence: 86%
“…Two studies showed a decrease in cortisol levels (Genner & Weston, 2014;Weakley et al, 2017). Two other studies (Sinclair et al, 2013;Anderson et al, 2016) showed an increase and decrease. One study (Sinclair et al, 2013) showed an increase in cortisol levels in men and a decrease in women.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation